Between images - Marques, Ivânia; Sgobin, Alexsandro (Geografares, 2014)
In this article we bring an invitation: to relate to the space through the production of images. A dialogue among images, taken at two points: first, a series of photographs that received transformations in digital media, and then used in geography lessons of elementary education in public schools in Campinas, São Paulo; and the second, with images created using “pinhole cameras”, built by hand, taken in high school in a city of Americana, São Paulo. What trips were and are possible with these images? What erasures, which rhizomes were asked effectively and arose, and did not, for what reasons the power was not effective. Keywords: territory; photography; experimentation.